Futsal Application Products: WEB based Integrated System (FTS) - Saud, Syauqi; Bessy Sitorus Pane; Amir Supriadi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The goal of this project is to create a web-based futsal integrated system (FTS) application. This application will function as a database for clubs affiliated with the North Sumatra district and province futsal associations. The present study employs a research and development process, utilizing nine research steps to build products that aim to address current database system difficulties. Group I test results on 15 trial samples with a total score of 3.90 divided by the maximum score resulted in a presentation of 78.33% with the eligible criteria. Group II trials on 30 Medan City Askot administrators showed that the effectiveness aspect was 93%, the quality aspect was 93.33%, and the product satisfaction aspect was 95% with an average percentage of 93.77% in the "Very Appropriate" category. These results were the product of two stages of the research project. The conclusion is that AFP North Sumatra can use this WEB-based system integrated futsal application product as a database to track the number of athletes, competitions, scheduling, club activities, and rankings for official tournaments held under its sponsorship. In addition, the public can learn about the size of Futsal's population and development, particularly in North Sumatra. application of information and technology to help realize the goals of the rapidly expanding globalization period.